In-Situ Fabrication of SnO2 Nanowires/Carbon Nanotubes Heterojunctions Based NO2 Gas Sensors - Quan, Thi Minh Nguyet; Nguyen, Van Duy; Chu, Manh Hung; Nguyen, Van Hieu (Old Journal, 2017)
Heterojunctions of metal oxides and single-walled carbon nanotubes (SWCNTs) have attracted great attention because of their unique physical properties and giant potential applications. In this study, we report the fabrication of NO2 gas sensors using heterojunctions made of SnO2 nanowires and SWCNTs. The single crystal SnO2 nanowires were grown on Pt electrodes via thermal evaporation. A thin film of SWCNTs was synthesized directly on top of the SnO2 nanowires to form the SnO2/SWCNTs heterojunctions by arc-discharge method. The morphology and characteristics of the SnO2/SWCNTs heterojunctions were characterized by a scanning electron microscopy (SEM) and a Raman spectroscopy. Current-voltage (I-V) characteristics and gas sensing properties of the SnO2/SWCNTs device were investigated. Results point out that the response of the SnO2/SWCNTs device was very high compared to that of individual materials, reaching up to when exposed to 1 ppm NO2 at 100 ℃.